The Pengembangan Trigonal Pensil Dalam Meningkatkan Kemampuan Menulis pada Anak Usia Dini: - - Noor, Fu'ad Arif; Amaliyah (Rumah Riset Publisher, 2025)
This study aims to improve fine motor skills through writing activities using trigonal pencil media in group A RA Tunas Bangsa Sidogemah Sayung Demak. The type of research used is Classroom Action Research. This research was conducted collaboratively between researchers and teachers. The subjects of this study were group A children, totaling 27 children, consisting of 10 boys and 17 girls. Data collection techniques with observation. The results showed that: The implementation of children's learning in fine motor writing can increase after being given action through writing activities using trigonal pencil media. Improvement of children's fine motor skills in writing using a trigonal pencil so that it is easier for children to hold a pencil in learning. This is shown by the results of the pre-cycle of children's fine motor skills classically on the BSB criteria, which is 26%. In the first cycle increased to 33% of children with good criteria and in the second cycle increased to 45% of children with good criteria. In the BSH criteria, which is 37%, in the first cycle it increases to 41% and in the second cycle it becomes 33%. The MB criteria are 26%, in the first cycle it becomes 19% and in the second cycle it becomes 15%. The MB criteria are 11%, in the first cycle it becomes 7% and in the second cycle it remains 7%.